Pembelajaran daring menggunakan pendekatan saintifik melalui media mind mapping pada materi bangun ruang untuk pemahaman siswa kelas 5 SDN Pakuhaji - Sintana, Fadila; Murni, Sukma; Widianto, Febri Restu (IKIP Siliwangi, 2025)
This research is a qualitative descriptive study to prove that the use of mind mapping media is able to help students understand learning, especially in cubes and blocks in online learning. The location of this research is SDN Pakuhaji. This study uses a scientific approach with the steps of stating the problem, collecting information, taking hypotheses, conducting experiments, collecting data, and drawing conclusions. From the results that have been obtained this mind mapping media can help students understand learning. During the pre-test the average score of the students was 2.2, while during the post-test the average score of the students increased by 6.6. There are difficulties experienced by students and writers in carrying out research, including lack of internet data, poor signal, and lack of mobile phone facilities.